Three essays on the financial behaviors of soldiers before and after deployment - Bell, Mary M. (Kansas State University, 2013)
The current three essay dissertation researched the financial behaviors of military service members before and after deployment using primary data collected at a Midwestern U.S. Army installation. The introduction (Chapter 1) reviewed the two financial surveys administered to Soldiers before (N = 701) and after (N = 670) they left for a yearlong deployment to a war zone. The first essay (Chapter 2) explored the financial behaviors, financial knowledge, and financial anxiety as they relate to rank and deployment. The results suggested that financial behaviors after deployment (Time 2) were significantly better than financial behaviors before deployment (Time 1). Rank had a positive effect on increased subjective financial knowledge where all ranks above privates (E1 to E2) had greater financial knowledge. Privates first class, specialists, and corporals (E3 to E4) had significantly lower financial knowledge than their direct supervisors, sergeants and staff sergeants (E5 to E6). Finally, Soldiers reported more financial anxiety before deployment (Time 1) than after deployment (Time 2). Using the framework of social learning theory, the second essay (Chapter 3) expanded the research of military financial behaviors before deployment to more fully understand stress and other factors that influence financial behavior outcomes. Results suggested that past behaviors and some personal factors played a significant role in Soldiers’ financial behaviors. Higher levels of subjective financial knowledge, more internal locus of control, and lower levels of financial anxiety all had a positive effect on financial behavior outcomes. The past behaviors variable had the most explanatory value in Soldiers’ financial behaviors before deployment. Soldiers with any amount of credit card debt had worse financial behaviors compared to Soldiers with no credit card debt, while Soldiers with greater amounts of emergency financial savings were more likely to have better financial behaviors than those who did not have any emergency financial savings. The final essay (Chapter 4) studied the factors that influenced financial behavior outcomes of both Soldiers and college students. This essay used primary data from a college student sample to compare to the before deployment (Time 1) survey data of Soldiers. Findings reported that past behaviors and some personal factors played a significant role in the financial behavior outcomes. Soldiers and college students with higher levels of subjective financial knowledge, more internal locus of control, and lower financial anxiety reported positive financial behaviors The most explanatory concept was that of past behaviors, which revealed that participants with no credit card debt had better financial behaviors compared to respondents who had any level of credit card debt. The conclusion (Chapter 5) highlights the findings of all three essays, which contribute both to the financial behavior literature. These papers also contribute to the research on the personal financial matters of service members. The research has direct implications for policy makers, military leaders, service providers, and financial planners and counselors.
Keywords: Deployment; Financial behavior; Military; Financial anxiety; Financial knowledge; Social learning theory; Education Finance (0277); Military Studies (0750)